Central and peripheral clocks are coupled by a neuropeptide pathway in Drosophila - Mareike Selcho (Nature Portfolio, 2017)
The emergence of the adult fruit flies from the pupae is jointly regulated by the central and peripheral clocks. Selchoet al. show that synchronization of the two clocks is mediated by the master clock brain neurons producing sNPF, and non-clock PTTH neurons that regulate the peripheral clock producing the steroid moulting hormone, ecdysone.